Innovation and creativity in HRD to increase economic growth of biotechnology companies by Helix Model - Farid, Hadi; Silong, Abu Daud; Shahmandi, Elham (2011)
This paper aims to discuss the relevance of creativity of Human Resource Development (HRD) and examine the effect of economic growth in biotechnology companies by Triple Helix Model and the System theory in Malaysia. Creative Enterprise in Malaysia is analyzed based on theoretical approaches. Knowledge is evolved and the relationships between all variables are illustrated. The country needs to enhance interactions to more institutes to develop technological capabilities and also to support specific programs to achieve economic growth in biotechnology companies.